Theoretical Study of the Antioxidant Activity of Quercetin Oxidation Products - Vásquez-Espinal, Alejandro; Yañez, Osvaldo; Osorio, Edison; Areche, Carlos; García-Beltrán, Olimpo; Ruiz, Lina María; Cassels, Bruce K.; Tiznado, William (Frontiers in Chemistry, 2019)
It was recently shown that, when tested in cellular systems, quercetin oxidized products (Qox) have significantly better antioxidant activity than quercetin (Q) itself. The main Qox identified in the experiments are either 2,5,7,3′,4′-pentahydroxy-3,4-flavandione (Fl) or its tautomer, 2-(3,4-dihydroxybenzoyl)-2,4,6-trihydroxy-3(2H)-benzofuranone (Bf). We have now performed a theoretical evaluation of different physicochemical properties using density functional theory (DFT) calculations on Q and its main Qox species. The most stable structures (for Q and Qox) were identified after a structural search on their potential energy surface. Since proton affinities (PAs) are much lower than the bond dissociation enthalpies (BDEs) of phenolic hydrogens, we consider that direct antioxidant activity in these species is mainly due to the sequential proton loss electron transfer (SPLET) mechanism. Moreover, our kinetic studies, according to transition state theory, show that Q is more favored by this mechanism. However, Qox have lower PAs than Q, suggesting that antioxidant activity by the SPLET mechanism should be a result of a balance between proclivity to transfer protons (which favors Qox) and the reaction kinetics of the conjugated base in the sequential electron transfer mechanism (which favors Q). Therefore, our results support the idea that Q is a better direct antioxidant than its oxidized derivatives due to its kinetically favored SPLET reactions. Moreover, our molecular docking calculations indicate a stabilizing interaction between either Q or Qox and the kelch-like ECH-associated protein-1 (Keap1), in the nuclear factor erythroid 2-related factor 2 (Nrf2)-binding site. This should favor the release of the Nrf2 factor, the master regulator of anti-oxidative responses, promoting the expression of the antioxidant responsive element (ARE)-dependent genes. Interestingly, the computed Keap1-metabolite interaction energy is most favored for the Bf compound, which in turn is the most stable oxidized tautomer, according to their computed energies. These results provide further support for the hypothesis that Qox species may be better indirect antioxidants than Q, reducing reactive oxygen species in animal cells by activating endogenous antioxidants.D